2013
DOI: 10.1088/0031-8949/88/02/025602
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of cadmium telluride films grown by glancing angle deposition

Abstract: Cadmium telluride films were grown by the glancing angle deposition (GLAD) technique. The samples were prepared under different incident deposition flux angles (α = 0°, 20° and 70° measured from the normal to the substrate surface). During deposition, the substrate temperature was maintained at room temperature. The structural study was performed using an x-ray diffraction diffractometer. The samples were found to be poly-crystalline with cubic structure for those deposited at α = 0° and 20° and hexagonal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…In our case, it is realized that with the increase of deposition angle and consequently thickness decrement, the equivalent band gap energy of the samples has increased form 2.06 to 2.24 eV. Similar results have been observed for other materials [27,29,47]. The direct bandgap energy values are close to the reported values for ZnTe thin films [48][49][50] .…”
Section: Optical Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…In our case, it is realized that with the increase of deposition angle and consequently thickness decrement, the equivalent band gap energy of the samples has increased form 2.06 to 2.24 eV. Similar results have been observed for other materials [27,29,47]. The direct bandgap energy values are close to the reported values for ZnTe thin films [48][49][50] .…”
Section: Optical Propertiessupporting
confidence: 90%
“…As shown in figure 4(a), the transmission spectra of samples represent an oscillatory behavior due to the construction and destruction interferences of incident light between air-films and film-glass interfaces. However, a considerable decrement is observable at higher GLAD produced thin films, which has also been reported for CdTe thin films by the authors of this article [47]. Also, as one can see in figure 4(a), upon increasing the deposition angle in the as-prepared samples a redshift trend happens, which might be as a result of decreasing the packing density of films in the porous samples [48].…”
Section: Optical Propertiessupporting
confidence: 85%
“…While e-beam evaporation has been used for the deposition of a large variety of materials, including amorphous and crystalline semiconductors [80,86,106,139,140], metals [29,[141][142][143][144][145][146], oxides [48,79,89,[147][148][149] and even molecular materials [71,103,150], MS has been the most widely used method for the deposition of metals and oxides when control over the crystalline structure and/or surface roughness is an issue.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Assessment of micro-pores is less straightforward, as these must be distributed within the interior of the nanocolumns. Nevertheless, the pore size distribution and surface area of Co-Cu IBAD Change of crystalline structure from hcp to fcc by ion beam irradiation [199] Co-Cr Evaporation and MS c-axis oriented along the nanocolumn axis [257] Cd-Te Evaporation Change from cubic to hexagonal structure depending on zenithal angle [139] AlN MS Sudden development of a preferential (0 0 0 2) orientation along the nanocolumn axis with the concentration of N 2 in the plasma gas [171] MS Variation of c-axis (0 0 0 2) orientation with geometry and other parameters [165] CrN MS Preferential formation of (0 0 1) films on single crystal MgO (0 0 1) [ different oxides has been determined by Flaherty et al [231] using a similar adsorption system consisting of a quartz crystal monitor and different vapors condensed at room temperature. This confirmed that the maximum internal surface area per unit volume occurs when a ¼ 75 .…”
Section: Porosity and Adsorption Propertiesmentioning
confidence: 99%
“…El método propuesto por R. Swanepoel en 1983 permite la determinación de propiedades ópticas de películas delgadas (Swanepoel 1983). Este método puede ser usado para evaluar el índice de refracción, espesor, índice de absorción, coeficiente de extinción y brecha de energía prohibida óptica ( gap ) de películas delgadas sobre sustratos transparentes (Sánchez-González et al 2006, Ragina et al 2011, Dorranian et al 2012, Ehsani et al 2013 Por otra parte, se han llevado a cabo trabajos exhaustivos con el propósito de verificar las condiciones de favorabilidad del uso de películas delgadas de Cu3BiS3 como capa absorbente en dispositivos fotovoltaicos (Estrella et al 2003, Gerein Cálculo de constantes ópticas de películas delgadas de Cu 3 BiS 3 a través del método de Wolfe original article a,b, Mesa et al 2009, Mesa et al 2010. Uno de los aspectos relevantes del trabajo de caracterización de películas delgadas es, sin lugar a dudas, la determinación de constantes ópticas que constituye una de las fases iniciales para la aplicación del compuesto Cu3BiS3 en celdas solares.…”
Section: Introductionunclassified